2020
DOI: 10.1177/0192623320947075
|View full text |Cite
|
Sign up to set email alerts
|

Local Tolerance and Biodegradability of a Novel Artificial Dura Mater Graft Following Implantation Onto a Dural Defect in Rabbits

Abstract: Dura mater defects are a common problem following neurosurgery. Dural grafts are used to repair these defects; among them are biodegradable polymeric synthetic grafts. ArtiFascia is a novel synthetic and fibrous Dural graft, composed of poly(l-lactic-co-caprolactone acid) (PLCL) and poly(d-lactic-co-caprolactone acid). In this study, the biodegradability and local tolerance of ArtiFascia was evaluated in rabbits and compared with a bovine collagen matrix as a reference control. ArtiFascia implantation resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…According to reports, dural defects are not uncommon in neurosurgery, and they are an important factor in inducing cerebrospinal fluid leakage, intracranial infection, meningitis, encephalocele, and epilepsy. Therefore, a series of studies have been carried out for dural repair to reduce the risk of clinical treatment [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…According to reports, dural defects are not uncommon in neurosurgery, and they are an important factor in inducing cerebrospinal fluid leakage, intracranial infection, meningitis, encephalocele, and epilepsy. Therefore, a series of studies have been carried out for dural repair to reduce the risk of clinical treatment [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of a new delivery device should include well-designed, regulated in vivo safety and toxicity studies. [37][38][39][40][41][42][43][44][45] Therefore, we performed two animal safety studies, one in rats another in cynomolgus monkeys, which historically have been used in safety evaluation studies and are recommended by appropriate regulatory agencies. Furthermore, it was essential to test whether the use of TRH in an intranasal route of administration can lead to any adverse events, since there is very little information on the in vivo safety of TRH when given intranasally.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, biodegradable implants are generally known for their low risk to cause inflammatory reactions, if there is no need to remove them [ 253 ]. Numerous studies have demonstrated the absence of inflammatory reactions in biodegradable implants [ 254 , 255 ]. However, if it is necessary to extract a biodegradable implant for one reason or another, the risk of inflammatory reactions increases [ 256 ], although in recent times the need for the extraction of biodegradable implants is becoming less frequent [ 257 , 258 ].…”
Section: Materials and Technologiesmentioning
confidence: 99%